Circadian and circannual rhythms of T3 and T4 secretions in Polwarth-Ideal rams - Souza, MIL; Bicudo, Sony Dimas [UNESP]; Uribe-Velasquez, L. F.; Ramos, Alcides Amorim [UNESP] (Elsevier B.V., 2002)
Plasma concentrations of triiodothyronine (T-3) and thyroxine (T-4) in five adult Polwarth-ldeal rams located at latitude 22degrees51 'S and longitude 48degrees26'W were evaluated every 2 months for 1 year (June, August, October, December, February, April). Blood collections were made at 2 h intervals for 24 h in each month, and hormone determinations were by radioimmunoassay. Means of T-3 (97.52 +/- 21.45 ng/dL) and T-4 (4.30 +/- 0.94 mug/dL) varied in peaks throughout the 24 h period with the highest concentrations occurring in the afternoon (16:30 and 14:30 h, respectively), and throughout the year where the highest levels were during months of long daylengths (October, December, February). Results suggest circadian and circannual rhythms in thyroid hormone secretion may be present in rams kept relatively close to the equator. (C) 2002 Published by Elsevier B.V. B.V.
Keywords: ovine; thyroid hormones; seasonality